Preserved C-peptide is common and associated with higher time in range in Chinese type 1 diabetes - Liu, Wei; Fang, Yayu; Cai, Xiaoling; Zhu, Yu; Zhang, Mingxia; Han, Xueyao; Li, Juan; Yin, Sai; Cai, Deheng; Chen, Jing; Wang, Lei; Shi, Dawei; et al. (Frontiers in Endocrinology, 2024)
OBJECTIVE To determine the residual C-peptide level and explore the clinical significance of preserved C-peptide secretion in glycaemic control in Chinese individuals with type 1 diabetes (T1D). RESEARCH DESIGN AND METHODS A total of 534 T1D participants were enrolled and divided into two groups, low C-peptide (fasting C-peptide ≤10 pmol/L) and preserved C-peptide group (fasting C-peptide >10 pmol/L), and clinical factors were compared between the two groups. In 174 participants who were followed, factors associated with C-peptide loss were also identified by Cox regression. In addition, glucose metrics derived from intermittently scanned continuous glucose monitoring (isCGM) were compared between individuals with low C-peptide and those with preserved C-peptide in 178 participants. RESULTS Lack of preserved C-peptide was associated with longer diabetes duration, glutamic acid decarboxylase (GAD) autoantibody and higher daily insulin doses, after adjustment (OR 1.10 [IQR 1.06-1.14]; OR 0.46 [IQR 0.27-0.77]; OR 1.04 [IQR 1.02-1.06]).In the longitudinal analysis, the percentages of individuals with preserved C-peptide were 71.4%, 56.8%, 71.7%, 62.5%, and 22.2% over the five years of follow-up. Preserved C-peptide was also associated with higher time in range (TIR) after adjustment of diabetes duration (62.4 [IQR 47.3-76.6] vs. 50.3 [IQR 36.2-63.0] %, adjusted P = 0.003). CONCLUSIONS Our results indicate that a high proportion of Chinese T1D patients had preserved C-peptide secretion. Meanwhile, residual C-peptide was associated with favourable glycaemic control, suggesting the importance of research on adjunctive therapy to maintain β-cell function in T1D.